1999
DOI: 10.1017/s1368980099000269
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers of, and benefits to, healthy eating reported by a Spanish national sample

Abstract: Objective: A national survey was developed in order to assess the difficulties and the potential benefits that the adult Spanish population perceive when they try to eat a healthier diet and also to help nutrition educators to develop relevant and specific strategies to promote healthy eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 13 publications
(13 reference statements)
3
17
0
3
Order By: Relevance
“…It seems that it is difficult to give up favorite foods and substitute with healthy foods, especially if the individual is living with a family. This is similar to the results of studies in Kuwait and Spain where willpower was among the main barriers to adherence to a healthy diet 2123…”
Section: Discussionsupporting
confidence: 88%
“…It seems that it is difficult to give up favorite foods and substitute with healthy foods, especially if the individual is living with a family. This is similar to the results of studies in Kuwait and Spain where willpower was among the main barriers to adherence to a healthy diet 2123…”
Section: Discussionsupporting
confidence: 88%
“…This change in eating habits towards less healthy diets coincides with what has been observed for the general population in the CIHEAM/ with the aim of improving people's quality of life and making them more efficient (López et al, 1999) and to promote food included in the Mediterranean diet. According to Baldini et al (2009) creative thinkers in manufacturing and retailing could be essential for the development of new products within the Mediterranean tradition that could be embraced by consumers of all ages.…”
Section: Discussionsupporting
confidence: 78%
“…[30,31]. A number of studies have suggested that a lack of knowledge is a greater barrier to eating a healthy diet among those of lower education level [22,23]. Being overweight can also be perceived as a significant barrier to physical activity [32].…”
Section: Introductionmentioning
confidence: 99%